2019
DOI: 10.1111/jne.12813
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐induced hypoglycaemia suppresses pulsatile luteinising hormone secretion and arcuate Kiss1 cell activation in female mice

Abstract: Stress suppresses pulsatile luteinising hormone (LH) secretion in a variety of species,although the mechanism underlying this inhibition of reproductive function remains unclear. Metabolic stress, particularly hypoglycaemia, is a clinically-relevant stress type that is modelled with bolus insulin injection (insulin-induced hypoglycaemia).The present study utilised ovariectomised C57BL/6 mice to test the hypothesis that acute hypoglycaemia suppresses pulsatile LH secretion via central mechanisms.Pulsatile LH se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
2
7
0
2
Order By: Relevance
“…Indeed, prior studies have shown that a range of different acute stressors can change ARC Kiss1 mRNA levels as well cFos expression in these cells. 62,63,71 Interestingly, we find here that CVS does not impact upon Kiss1 mRNA expression in either hypothalamic population in mice and, similarly, 18 days of chronic stress has been reported to have no effect on hypothalmic Kiss1 mRNA in rats. 24 Thus, it remains unclear how CVS may be impacting upon pulsatile LH secretion, as is the case for the LH surge mechanism.…”
Section: F I G U R Esupporting
confidence: 71%
See 3 more Smart Citations
“…Indeed, prior studies have shown that a range of different acute stressors can change ARC Kiss1 mRNA levels as well cFos expression in these cells. 62,63,71 Interestingly, we find here that CVS does not impact upon Kiss1 mRNA expression in either hypothalamic population in mice and, similarly, 18 days of chronic stress has been reported to have no effect on hypothalmic Kiss1 mRNA in rats. 24 Thus, it remains unclear how CVS may be impacting upon pulsatile LH secretion, as is the case for the LH surge mechanism.…”
Section: F I G U R Esupporting
confidence: 71%
“…Because the ARC kisspeptin neurones represent the GnRH pulse generator, 70 it is likely that different stressors impact upon these cells. Indeed, prior studies have shown that a range of different acute stressors can change ARC Kiss1 mRNA levels as well cFos expression in these cells 62,63,71 . Interestingly, we find here that CVS does not impact upon Kiss1 mRNA expression in either hypothalamic population in mice and, similarly, 18 days of chronic stress has been reported to have no effect on hypothalmic Kiss1 mRNA in rats 24 .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Sex steroids from the ovaries regulate this axis through both positive and negative feedback mechanisms. Several studies implicate the gonadotrope as a point for nutrient regulation of the HPG-axis in addition to evidence that kisspeptin and GnRH neurons in the central nervous system regulate LH pulsatility in response to glucose availability 5 8 . In normal women and in women with polycystic ovary syndrome, BMI negatively correlates with circulating LH 9 .…”
Section: Introductionmentioning
confidence: 99%